Environmentally sustainable acid mine drainage remediation: Research developments with a focus on waste/by-products. (September 2018) - Moodley, I.; Sheridan, C.M.; Kappelmeyer, U.; Akcil, A.
Highlights: Acid mine drainage is a major environmental problem. Many prevention and treatment methods are available but are often impractical or costly to implement. The use of waste materials or bi-products from other industries may have substantial benefits. The use of these alternative materials represents an opportunity for AMD remediation to be environmentally sustainable. Abstract: Acid mine drainage (AMD) is a major environmental problem and remains so despite the availability of a vast array of remediation techniques and technologies. Many methods used to remediate AMD are limited in implementation due to poor performance, design inaccuracies, difficult understanding of functionality, high costs, usage of hazardous chemicals, depletion of natural resources and the generation of further waste. As a result of these limitations, and due to the need for sustainability, research is being conducted on the use of waste materials and by-products from other industries, such as the dairy, paper mill, steel mill, wine, tyre, seafood and even from AMD treatment itself, to remediate AMD. Materials from these industries have been shown to reduce or eliminate some of the drawbacks of conventional techniques and technologies such as lime neutralization, passivation, in-situ biological remediation, backfilling, waste-heap covers, adsorption, constructed wetlands, desalination, sulfidogenic bioreactors, anoxic limestone drains and permeable reactive barriers. This paper presents an overview of AMD and discusses research developments into various waste materials or by-products from other industries that have been successfully applied in remediating AMD.